Manajemen Persediaan Bahan Baku Pada UMKM Gavrillo Klappertart dan Cookies - Leatomu, Nevy L; Timisela, Natelda R; Parera, Weldemina B (Universitas Pattimura, 2024)
Inventory management is a crucial aspect that greatly affects business continuity. Raw material inventory, especially in manufacturing companies, is considered a major need because disruptions in raw material inventory can disrupt the entire company's operations. The purpose of this study is to understand raw material inventory management in UMKM Gavrillo Klappertart and Cookies. The findings indicated that the management of young coconut raw material inventory continues to rely on traditional approaches. The research methodology employed in this study is qualitative and descriptive in nature. In this context, researchers describe and provide an understanding of raw material inventory management in UMKM Gavrillo Klappertart and Cookies, as well as analyze the obstacles faced using a qualitative approach.